2014
DOI: 10.1111/1462-2920.12419
|View full text |Cite
|
Sign up to set email alerts
|

The Yersinia pestisHmsCDE regulatory system is essential for blockage of the oriental rat flea (Xenopsylla cheopis), a classic plague vector

Abstract: SUMMARY The second messenger molecule cyclic diguanylate (c-di-GMP) is essential for Y. pestis biofilm formation that is important for blockage-dependent plague transmission from fleas to mammals. Two diguanylate cyclases (DGCs) HmsT and Y3730 (HmsD) are responsible for biofilm formation in vitro and biofilm-dependent blockage in the oriental rat flea Xenopsylla cheopis, respectively. Here, we have identified a tripartite signaling system encoded by the y3729-y3731 operon that is responsible for regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 58 publications
(117 reference statements)
0
37
1
1
Order By: Relevance
“…yfiRNB are in a single operon in E. coli, and YfiR and YfiN have similar activities in E. coli as those in P. aeruginosa (51)(52)(53)59). Previous work has also shown that the YfiN homolog AwsR controls Pseudomonas fluorescens cellulose and biofilm formation (60), and in Yersinia pestis, the YfiN and YfiR homologs, HmsD and HmsC, respectively, contribute to biofilm formation and the blockage of blood intake in the rat flea Xenopsylla cheopis (61,62). The inhibition of YfiN by YfiR can be overcome in P. aeruginosa via overexpression of the outer membrane protein YfiB, which sequesters YfiR away from YfiN (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…yfiRNB are in a single operon in E. coli, and YfiR and YfiN have similar activities in E. coli as those in P. aeruginosa (51)(52)(53)59). Previous work has also shown that the YfiN homolog AwsR controls Pseudomonas fluorescens cellulose and biofilm formation (60), and in Yersinia pestis, the YfiN and YfiR homologs, HmsD and HmsC, respectively, contribute to biofilm formation and the blockage of blood intake in the rat flea Xenopsylla cheopis (61,62). The inhibition of YfiN by YfiR can be overcome in P. aeruginosa via overexpression of the outer membrane protein YfiB, which sequesters YfiR away from YfiN (53).…”
Section: Discussionmentioning
confidence: 99%
“…4A and B). In Y. pestis, biofilm formation was only modestly affected by deletion or overexpression of the YfiB homolog HmsE (61,62). In UPEC strain CFT073, yfiR deletion leads to an increase in cellulose and curli production along with attenuation of bladder and kidney titers in a murine urinary tract infection (UTI) model (52).…”
Section: Discussionmentioning
confidence: 99%
“…The role of c‐di‐GMP in pathogenesis has been extensively studied in a number of animal and human bacterial pathogens, including Salmonella enterica (Hisert et al ., ; Lamprokostopoulou et al ., ), Vibrio cholerae (Tischler and Camilli, ), Yersinia pestis (Bobrov et al ., 2011; 2014) and P. aeruginosa (Kulasakara et al ., ; Ryan et al ., ; Li et al ., ). Pseudomonas aeruginosa is a versatile Gram‐negative bacterium that can be found in various environments, including soil, water and vegetation (Lyczak et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that when the rats die from plague infection their hungry fleas have little choice but to feed from humans, and this spreads the disease (Schotthoefer et al, 2011;Chouikha and Hinnebusch, 2012;Bobrov et al, 2014). The Black Death was the second pandemic of bubonic plague, and swept across medieval Europe from 1348 to 1352.…”
Section: Ectoparasites In Medieval Europementioning
confidence: 99%